Multimodal delivery of irinotecan from microparticles with two distinct compartments - Rahmani, Sahar (J Control Release, 2013)
In the last several decades, research in the field of drug delivery has been challenged with the fabrication of carrier systems engineered to deliver therapeutics to the target site with sustained and controlled release kinetics. Herein, we report the fabrication of microparticles composed of two distinct compartments: i) one compartment containing a pH responsive polymer, acetal-modified dextran, and PLGA (polylactide-co-glycolide), and ii) one compartment composed entirely of PLGA. We demonstrate the complete release of dextran from the microparticles during a 10-hour period in an acidic pH environment and the complete degradation of one compartment in less than 24 h. This is in congruence with the stability of the same microparticles in neutral pH over the 24-hour period. Such microparticles can be used as pH responsive carrier systems for drug delivery applications where their cargo will only be released when the optimum pH window is reached. The feasibility of the microparticle system for such an application was confirmed by encapsulating a cancer therapeutic, irinotecan, in the compartment containing the acetal-modified dextran polymer and the pH dependent release over a 5-day period was studied. It was found that upon pH change to an acidic environment, over 50% of the drug was first released at a rapid rate for 10 h, similar to that observed for the dextran release, before continuing at a more controlled rate for 4 days. As such, these microparticles can play an important role in the fabrication of novel drug delivery systems due to the selective, controlled, and pH responsive release of their encapsulated therapeutics.